A Matched Case Control Study of Surgically and Non-surgically Treated Patent Ductus Arteriosus in Extremely Pre-term Infants - Olsson, Karl Wilhelm; Youssef, Sawin; Kjellberg, Mattias; Raaijmakers, Renske; Sindelar, Richard (Frontiers in Pediatrics, 2021)
There are still uncertainties about the timing and indication for surgical ligation of patent ductus arteriosus (PDA) in preterm infants, where lower gestational age (GA) usually is predictive for surgical treatment. Our aim was to assess differences in clinical characteristics and outcomes between surgically treated and matched non-surgically treated PDA in extremely preterm infants. All extremely preterm infants born 2010-2016 with surgically treated PDA (Ligated group; n=44) were compared to non-surgically treated infants (Control group; n=44) matched for gestational age (+/-1 week) and time of birth (+/- 1 month). Perinatal parameters, echocardiographic variables, details of pharmacological PDA treatment, morbidity and mortality were assessed. Mean GA and birthweight were similar between the Ligated group (24+5±1+3 weeks and 668±170 grams) and the Control group (24+5±1+3 weeks and 704±166 grams; p=1.000 and p = 0.319, respectively). Infants in the Ligated group had larger ductal diameters prior to pharmacological treatment, and lack of diameter decrease and PDA closure after treatment (p=0.022, p=0.043 and 0.006, respectively). Transfusions, postnatal steroids and invasive respiratory support were more common in the Ligated group. Except for a higher incidence of severe bronchopulmonary dysplasia (BPD) in the Ligated group there were no other difference in outcomes or mortality between the groups. Early large ductal diameter and reduced responsiveness to pharmacological treatment predicted the need for future surgical ligation in this matched cohort study of extremely preterm infants where the effect of GA and differences in treatment strategies were excluded. Besides an increased incidence of sever BPD in the Ligated group, no other differences in morbidity or mortality were detected.